Evaluate the Behavior of Industry Workers toward Safety and their Impacts in Environment (Global Journals of Research in Engineering, 2023)
In this paper evaluated the behavior of the workers in the industry toward safety conducted among workers in workshops and factories in the Omdurman industrial area to identify and highlight the behaviors of workers toward occupational health and safety and their impacts on the environment Data were collected through a questionnaire given to 58 workers to explain the attitudes and practices of workers and tanker drivers were observed Interviews were conducted with number of decision-makers in several departments concerned with the environmental impacts of industry The workshops studied included welding carpentry car repairing and disposal and restoring batteries Related hazards were identified and classified The caught in or between things had the highest incidence the machines were the primary cause of fractures amputation and wounds 17 2 15 5 24 2 respectively Equipment was leading the main cause of burn and contusive from the heat source 8 6 12 1 respectively Hazardous materials was the fundamental cause of poisonous from a chemical birth sources coma and death 13 8 6 9 respectively
Keywords: safety; occupational health; worker; industry; unsafe acts; accident